2010
DOI: 10.1007/s10681-010-0166-3
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping for developmental behavior of plant height in wheat (Triticum aestivum L.)

Abstract: A recombinant inbred line (RIL) population with 305 lines derived from a cross of Hanxuan 10 9 Lumai 14 was used to identify the dynamic quantitative trait loci (QTL) for plant height (PH) in wheat (Triticum aestivum L.). Plant heights of RILs were measured at five stages in three environments. Total of seven genomic regions covering PH QTL clusters on different chromosomes identified from a DH population derived from the same cross as the RIL were used as the candidate QTLs and extensively analyzed. Five addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 30 publications
5
38
0
1
Order By: Relevance
“…Similar results have been reported by Wang [25]. We also found that the QTLs detected by both conditional and unconditional analysis in both years showed slight differences, such as QHt-3B, which was More importantly, these unstable QTLs might be more sensitive to the environment than QTLs detected at the same stages in the two years.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results have been reported by Wang [25]. We also found that the QTLs detected by both conditional and unconditional analysis in both years showed slight differences, such as QHt-3B, which was More importantly, these unstable QTLs might be more sensitive to the environment than QTLs detected at the same stages in the two years.…”
Section: Discussionsupporting
confidence: 90%
“…These studies indicated that the actions and interactions of genes responsible for plant height varied in different growth periods and environmental conditions. Recently, QTL mapping for developmental behavior of plant height in wheat was conducted under well-watered and drought conditions [25].…”
mentioning
confidence: 99%
“…The conditional mapping method has been used to map QTL for plant height in maize (Yan et al 2003), brown plant hopper resistance in rice (Ren et al 2004), pod number and the main stem and plant height of soybean (Sun et al 2006), seed weight of soybean (Teng et al 2009), plant height of wheat (Cui et al 2011;Wang et al 2010) and linolenic acid content of soybean seed (Han et al 2011). But, so far, there is no report on the use of conditional QTL mapping to reveal the dynamics of plant disease resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic assessments of plant height in wheat were carried out in many studies (Cadalen et al 1998;Korzun et al 1998;Peng et al 2003;Schnurbusch et al 2003;McCartney et al 2005;Pestsova et al 2006;Quarrie et al 2006;Wang et al 2010;Wu et al 2010), but most of the data were collected only at or near maturity. The combination of developmental quantitative genetics with molecular markers make it possible to analyze the developmental behavior of important agronomic traits (Price and Tomos 1997;Yan et al 1998aYan et al , 1998bYan et al , 2003Levesque et al 2006;Wang et al 2010;Wu et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of developmental quantitative genetics with molecular markers make it possible to analyze the developmental behavior of important agronomic traits (Price and Tomos 1997;Yan et al 1998aYan et al , 1998bYan et al , 2003Levesque et al 2006;Wang et al 2010;Wu et al 2010). For most analyses, the extra genetic effect from time (t -1) to time t was the D-value (different value) of genetic effects at time t and time (t -1), i.e., unconditional analysis.…”
Section: Introductionmentioning
confidence: 99%